Internalisasi Nilai-nilai Moderasi Beragama dalam Karya Sastra - Afryansyah (Prodi Studi Agama-agama Fakultas Ushuluddin dan Dakwah IAIN Kediri, 2022)
The urgency of mainstreaming religious moderation can be carried out in various activities and internalizing in multidisciplinary Sciences. Literary works are considered capable of containing the values of religious moderation. The purpose of this paper is to describe the internalization of religious moderation values in literary works. To achieve this goal, the study of literature with the approach of sociology and literary psychology. Based on these studies, nine values of religious moderation were found, namely: (1) middle - middle (tawassuth), (2) upright (I'tidal), (3) tolerance (tasamuh), (4) deliberation (Shura), (5) reform (ishlah), (6) pioneering (qudwah), (7) citizenship/love of the homeland (muwathanah), (8) anti-Violence (al-la'unf), and (9) friendly culture (I'tibar al-‘urf). These values can be internalized in literary works, whether poetry, prose or drama. In the literary approach, the value of religious moderation influences the psychology and sociology of literature (author and reader) and vice versa. In other words, what is produced (the value of religious moderation) in literary works is the influence of the sociological and psychological author, then the value of religious moderation affects the psychological reader to form the social environment (society). For this reason, the internalization of the value of religious moderation can be done through intrinsic and extrinsic elements of literary works by authors and through literary learning.